2017
DOI: 10.4288/kisoron.44.1-2_55
|View full text |Cite
|
Sign up to set email alerts
|

What Is Mental Illness?

Abstract: The concept of mental illness has been challenged by various parties and with various background concerns. In this paper,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Schizophrenia is a severe, debilitating chronic psychiatric disorder that causes impairments in cognition, speech, thinking and emotional responsiveness 1. It impairs individuals’ social and occupational functioning, as well as limits their ability to carry out daily activities 2. For instance, Wiersma et al conducted a 15-year multicentre survey in Europe and found that social dysfunction was widespread and persistent in schizophrenia 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia is a severe, debilitating chronic psychiatric disorder that causes impairments in cognition, speech, thinking and emotional responsiveness 1. It impairs individuals’ social and occupational functioning, as well as limits their ability to carry out daily activities 2. For instance, Wiersma et al conducted a 15-year multicentre survey in Europe and found that social dysfunction was widespread and persistent in schizophrenia 3.…”
Section: Introductionmentioning
confidence: 99%
“…1 It impairs individuals' social and occupational functioning, as well as limits their ability to carry out daily activities. 2 For instance, Wiersma et al conducted a 15-year multicentre survey in Europe and found that social dysfunction was widespread and persistent in schizophrenia. 3 Similar findings were also reported in China.…”
Section: Introductionmentioning
confidence: 99%